2022
DOI: 10.1097/cco.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic psychosocial interventions for patients with cancer and their caregivers: an update

Abstract: Purpose of reviewCancer causes significant impacts on patients and their caregivers. Cancer is also associated with multiple physical and emotional challenges for the patient-caregiver dyad. This patient-caregiver dyad should be considered as a unit of care by healthcare providers and supported through dedicated psychological interventions.Recent findingsTwelve studies that tested dyadic interventions aiming to support patient-caregiver dyads were identified from the period April 2020 to December 2021. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…In these interventions, a cancer dyad, consisting of both the cancer patient and their caregiver, are engaged as active participants. Findings suggested that the use of a dyadic approach yields positive outcomes in enhancing cancer dyads' general state of wellness, particularly with regard to the alleviation of depressive and anxious symptoms and the enhancement of quality of life (Otto et al., 2022; Tiete & Porter, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In these interventions, a cancer dyad, consisting of both the cancer patient and their caregiver, are engaged as active participants. Findings suggested that the use of a dyadic approach yields positive outcomes in enhancing cancer dyads' general state of wellness, particularly with regard to the alleviation of depressive and anxious symptoms and the enhancement of quality of life (Otto et al., 2022; Tiete & Porter, 2022).…”
Section: Introductionmentioning
confidence: 99%